An Open Radical Prostatectomy Approach that mimics the Technique of Robot-assisted Prostatectomy: A Comparison of Perioperative Outcomes. - özkaptan, orkunt; Balaban, Muhsin; Sevinc, Cuneyd; Karadeniz, Tahir (Urology Journal, 2019)
Purpose: To report on an ascending radical retropubic prostatectomy (RRP) technique and determine whether this technique has better perioperative, oncological and functional outcomes than the standard RRP technique applied in our clinic Material and Methods: The perioperative and functional outcomes of the 246 patients that underwent standard RRP (N = 150) or modified RRP (N = 96) were evaluated, retrospectively. In the modified RRP technique the dorsal vasculare complex (DVC) was controlled at first. Thereafter, the bladder neck was incised at the prostate-vesical junction. After seminal vesicles and vasa were exposed, posterior dissection was continued until to the apex. Finally, the urethra was divided. To assess the differences between the two groups the independent sample T-test and chi-square test were used. Results: The mean volume of estimated blood loss (EBL) was significantly longer in the standard RRP group than in the modified RRP group (610 vs. 210 ml, respectively; P= .001). The mean operative time (OT) was significantly less in the modified RRP group (177 vs. 134 min, respectively; P = .003), as were the transfusion rate TR (P = .041). With regard to the rate of postoperative complications, a statistically significant difference was observed between the two groups (P = .014). Continence rates after 3 and 12 months postoperatively were 98.95% and 98.95 % in the modified RRP group, and 97.33% and 98.66% in the standard RRP group, respectively ( P = .83). Conclusion: We observed that the EBL, TR and OT were significantly lower when we applied the modified RRP technique to patients. This modified technique might be applicable for institutions as an alternative procedure for the standard RRP technique.